Comparative Analysis of Romaka Lavana and Vida Lavana Prepared by Two Different Methods Using XRD and EDAX - Bibitha B; Sreeni T.V (International Journal of Ayurveda and Pharma Research, 2025)
Romaka Lavana and Vida Lavana are the two salts mentioned under Lavana varga in Ayurveda. Romaka Lavana is a naturally occurring salt, which is collected from the banks of Sambhar Salt Lake, Jaipur, Rajasthan. Vida lavana is a salt artificially prepared from Amalaki churna and Romaka lavana. Various methods for the preparation of Vida Lavana was mentioned in the classical Rasasastra textbooks. In the present study Rasatarangini reference was adopted. There are significant challenges to the classical method of preparation of Vida Lavana in terms of temperature, time consumed as well as yield of final product. Some of the challenges with the classical methodology can be addressed by an electric muffle furnace, which provides a more uniform and precisely regulated alternative. Hence two different heating pattern as well as time duration was adopted here to prepare Vida lavana using an Electric muffle furnace. The final products obtained from these methods and Romaka Lavana used for the preparation of Vida lavana were analysed by XRD and EDAX to determine the elemental composition. The study findings show that, the product obtained after the two methods predominantly contains sodium chloride.